The Cognitive Cartography of Cybersecurity: India’s Knowledge Pathways and Scholarly Networks - Dey, Kishore (Information Research Communications, 2025)
Purpose/Background This research employs a bibliometric study to understand the Indian scenario of cybersecurity research from 2016 to 2025. The paper deeply examines the research, and the research and development are the key focuses. Methodology The article has been based on an OpenAlex database inquiry, analysis by R (Bibliometrix/Biblioshiny), and Microsoft Excel. The investigation examined 3,374 Indian documents. Results The examination of 3,374 Indian documents has resulted in the finding of an extraordinary annual growth rate of 58.57% which was facilitate by the equally strong international collaboration trend and the dominance of journal articles and book chapters. SRM Institute of Science and Technology, Chitkara University, and Lovely Professional University were identified as top productive affiliations. The prominent keywords such as computer science, artificial intelligence, internet privacy, and machine learning indicate the technological and ethical side of the cybersecurity research in India, which are merging. Conclusion In essence, the discoveries delineate India’s intellectual and collaborative frameworks that mirror an at-depth-interdisciplinary knowledge ecosystem, which is growing and thus in line with the global digital security priorities.
Keywords: Artificial Intelligence; Bibliometrics; Cybersecurity; India; Knowledge Mapping; OpenAlex; Scholarly Collaboration.